HOST PLANT UTILIZATION BY BUTTERFLIES AT VISAKHAPATNAM - J. B. ATLURI,; D. SANDHYA DEEPIKA,; M. BHUPATHIRAYALU,; K. CHINNA RAO, (The Bioscan, 2011)
In the present study the butterfly fauna and their larval host plants at Andhra University campus, Visakhapatnam, Andhra Pradesh were described. At Andhra University campus 38 butterfly species distributed among 29 genera were observed belonging to 8 families i.e., Danaidae-3; Satyridae-3; Nymphalidae-11; Lycaenidae-6; Papilionidae- 7; Pieridae-6, Acraeidae -1 and Hesperiidae -1. These butterflies utilized 74 plant species as their larval host plants. Among the 38 butterfly species Euploea core core could utilize 8 host plant species, Neptis hylas 7; Junonia lemonias and Eurema hecabe simulata 6 each; Elymnias caudata, Acraea terpsicore, Junonia hierta and Princeps demoleus utilized 5 each. The remaining butterfly larvae utilized less than 5 host plant species except 2 species Everes lacturnus syntala and Barbo cinnara which could not be found to feed on any of the host plants available at the study site. Also the breeding behavior and season of each of the butterflies were described.